2020
DOI: 10.3389/fpls.2020.00339
|View full text |Cite
|
Sign up to set email alerts
|

Combating Climate Change in the Kenyan Tea Industry

Abstract: Climate change triggered by global warming poses a major threat to agricultural systems globally. This phenomenon is characterized by emergence of pests and diseases, extreme weather events, such as prolonged drought, high intensity rains, hailstones and frosts, which are becoming more frequent ultimately impacting negatively to agricultural production including rain-fed tea cultivation. Kenya is predominantly an agricultural based economy, with the tea sector generating about 26% of the total export earnings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 73 publications
1
9
0
Order By: Relevance
“…According to recent study, there is an increasing frequency of frost due to the climate change, which is detrimental to tea production (53)(54)(55). In this study, we observed that black, blue, and red shades all alleviated frost damage on tea plants within our experiment duration.…”
Section: Discussionsupporting
confidence: 63%
“…According to recent study, there is an increasing frequency of frost due to the climate change, which is detrimental to tea production (53)(54)(55). In this study, we observed that black, blue, and red shades all alleviated frost damage on tea plants within our experiment duration.…”
Section: Discussionsupporting
confidence: 63%
“…Climate change has led to extreme and unpredictable weather patterns, resulting in longer dry spells, heavy rainfall, more hail, higher temperatures, and increased attacks of pests and diseases (Marx et al., 2017). Therefore, effective tea‐breeding strategies that use genomic‐assisted breeding are needed to develop high‐yielding and high‐quality tea varieties that are also tolerant to biotic and abiotic stresses (Mondal, 2011; Muoki et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, diversification is greatly influenced by availability of suitable germplasm, wherein, anthocyanin-rich tea cultivars due to their pleasant taste and rich health beneficial compounds are getting global attention for production of “Specialty Tea” that can fetch premium prices to the farmers. Through breeding (natural or artificial hybridization) followed by clonal field selection, anthocyanin-rich tea cultivars (purple tea) have been developed for product diversification 5 , 6 . Anthocyanin, a water-soluble secondary metabolite synthesized in the cytosol and localized in vacuoles, is an important plant pigment responsible for the red, violet, purple and blue pigmentations in different plant tissues 7 .…”
Section: Introductionmentioning
confidence: 99%